Motor-type aphasia in English and Spanish and its relation to the linguistic variables intervening in reading. - Vereda-Alonso, Cristina; González-Sánchez, Mercedes (De Gruyter Poland, 2021)
This pilot study was designed to explore the way linguistic variables affect reading in English and Spanish in the context of motor-type aphasia. The participants were two speakers with English L1, two English-Spanish bilinguals, and four speakers with Spanish L1. The Boston Diagnostic Aphasia Examination (BDAE) and Psycholinguistic Assessments of Language Processing in Aphasia (PALPA) were used to assess the participants’ reading skills. L1 English, Spanish, and bilingual participants used both the lexical and sublexical route when reading, but utilized one route more than the other depending on their linguistic profile. L1 Spanish participants used the damaged phonological route, producing many neologisms or non-answers. L1 English participants, utilizing the lexical route, produced more lexicalizations than neologisms. The bilingual participants showed interlanguage interference by producing many spelling-sound regularizations. These results suggest that orthographic depth and different linguistic variables affect individuals with motor-type aphasia depending on the language they speak.
Keywords: Afasia; Dislexia; Lectura - Problemas de aprendizaje; Bilingüismo; Motor-type aphasia; Reading skills; Acquired dyslexia; Linguistic effects; Bilingualism